2009
DOI: 10.1002/pola.23359
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and degradation of biomedical materials based on linear and star shaped polyglycidols

Abstract: Linear and star shaped polyglycidols (synonym with polyglycerols) are prepared in a controlled ring opening polymerization of protected glycidols. Beside the molar mass and the polydispersity, the architecture of the polyglycidols is controlled by using mono-and multifunctional monoand polydispers initiators. Copolymers of dissimilarly protected glycidols as well as copolymers with nonfunctional oxiranes were prepared by means of anionic polymerization while copolymers of protected glycidol with tetrahydrofura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
97
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 86 publications
(100 citation statements)
references
References 110 publications
(124 reference statements)
1
97
0
2
Order By: Relevance
“…Metal alkoxide species, M-OR, have been shown to be the true active species in numerous ROP processes. [1][2][3][4][5][6][7][8][9][10][11][12][13][18][19][20][21][22][23][24] For example, in 2004, Lewiński and co-workers reported the first structurally characterized aluminum ε-caprolactone complex, indicating that the Al-Me group has poor reactivity with CL. 77 Thus, in most ROP cases, an alcohol is used as an initiator and is essential in order to start the polymerization.…”
Section: Introductionmentioning
confidence: 99%
“…Metal alkoxide species, M-OR, have been shown to be the true active species in numerous ROP processes. [1][2][3][4][5][6][7][8][9][10][11][12][13][18][19][20][21][22][23][24] For example, in 2004, Lewiński and co-workers reported the first structurally characterized aluminum ε-caprolactone complex, indicating that the Al-Me group has poor reactivity with CL. 77 Thus, in most ROP cases, an alcohol is used as an initiator and is essential in order to start the polymerization.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, based on previous reports, [5][6][7][8][9][10][11][12][13][18][19][20][21][22][23][24][25][26][27] after the insertion of the first equivalent of other monomers (CL, VL, and TMC), the rates of polymerization will not decrease remarkably, indicating that the insertion of the first monomers will not cause such a significant chelation effect like LA. Thus, in these cases, the energy of the initiation step can be used to estimate the energy of propagation.…”
mentioning
confidence: 99%
“…[16][17][18] A variety of functional polyglycidols were synthesized in our group by post polymerization modification of the hydroxymethyl groups obtained after deprotection or by conversion of the phenyl carbonate groups prepared as intermediates. [19][20][21][22] Based on these results we concluded that polyglycidols fulfill the prerequisites of being suitable precursors for the synthesis of amphiphilic doublecomb polymers via the grafting-onto strategy.…”
Section: Introductionmentioning
confidence: 88%